1992
DOI: 10.1042/bst020059s
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypothyroid rats with T2 (3,5-di-iodo-l-thyronine) rapidly stimulates respiration in subsequently isolated mitochondria

Abstract: Administration of T3 to hypothyroid rats increases the respiration rate of the subsequently isolated mitochondria [1,2]. This effect, and a number of other rapid effects of T3, occur

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We found that hypothyroid rats survived cold for 3–4 days, but when injected with 3,5‐T2 their cold tolerance was improved, with an effect on both the specific and total oxidase activity of the analysed organs, and the animals survived, like those treated with T3, for at least the duration of the treatment. However, the action of 3,5‐T2 does not affect the tissue trophism, and we, on the basis of previous studies (O'Reilly & Murphy 1992b, Goglia et al. 1994a,b), raised the possibility that the effects exerted by 3,5‐T2 may be mediated by its direct interaction with mitochondria.…”
Section: Thyroid Hormones and Coldmentioning
confidence: 67%
“…We found that hypothyroid rats survived cold for 3–4 days, but when injected with 3,5‐T2 their cold tolerance was improved, with an effect on both the specific and total oxidase activity of the analysed organs, and the animals survived, like those treated with T3, for at least the duration of the treatment. However, the action of 3,5‐T2 does not affect the tissue trophism, and we, on the basis of previous studies (O'Reilly & Murphy 1992b, Goglia et al. 1994a,b), raised the possibility that the effects exerted by 3,5‐T2 may be mediated by its direct interaction with mitochondria.…”
Section: Thyroid Hormones and Coldmentioning
confidence: 67%
“…3,5‐T 2 was initially shown to rapidly stimulate respiratory rate in isolated rat liver mitochondria (O'Reilly & Murphy ) and to enhance oxygen consumption in rat liver (Horst et al . ), but not glucose uptake in human mononuclear blood cells (Kvetny ).…”
Section: Diiodothyroninesmentioning
confidence: 99%
“…3,5-Diiodothyronine (3,5-T2) is a product of T3 outer ring deiodination that increases oxygen consumption in perfused rat liver (Horst et al, 1989), blood mononuclear cells (Kvetny, 1992) and rat liver mitochondria (Lanni et al, 1993;O'Reilly & Murphy, 1992), resembling the metabolic effects of T3 and T4. Remarkably, 3,5-T2 has been shown to prevent liver steatosis in rats fed a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%